(untitled) (Research, Society and Development, 2022)
Introduction: Climacteric is defined as the period between menacme and senility, with a period before and after menopause. The climacteric syndrome is defined by more intense signs and symptoms close to the menopause, most of which are due to the lack of circulating estrogen, in addition to psychosocial factors. In the 20th century, there were few health prevention and promotion campaigns for this part of the female population. Today, the Ministry of Health has programs aimed at these patients. It is known that the use of contraceptive methods improves symptoms and acts as a protective factor against endometrial neoplasms. However, this reality needs to be individualized, taking into account risk factors and women’s complaints. Objective: To analyze the contraceptive methods used by climacteric women in a UBS in western Paraná. Methodology: this is a quantitative analysis of women aged between 42 and 48 years old, registered in a Basic Health Unit in the West of Paraná. They answered a form sent via the social network WhatsApp, which included the free and informed consent form (ICF), requesting authorization and clarifying the research. Results: of the 31 women interviewed, all had a medical indication of contraceptive use, only 17 (54.8%) used it. Thus, a multidisciplinary approach in primary health care is extremely important, aimed at welcoming women at this stage of life, in addition to seeking changes in the life habits of this population, so that, in this way, it is possible to achieve a better quality of life.